No cognitive scarring over 20 years in recurrent depression: Bidirectionality of cognitive functioning and depression - Joost Gülpen; Amanda M. Legemaat; Eva A. M. van Dis; Gert J. Geurtsen; Ellie M. Wekking; Huibert Burger; Damiaan A. J. P. Denys; Claudi L. H. Bockting (Clinical Psychology in Europe, 2026)
Background Cognitive deficits are prevalent in major depressive disorder (MDD), span multiple cognitive domains, and often persist during remission. However, long-term associations between cognitive functioning and depression remain unclear. This study explores bidirectional associations using 20-year longitudinal data, providing follow-up twice as long as previously reported. Method Individuals in remission of recurrent MDD underwent neuropsychological assessments at baseline ( n = 137, 21-65 years) and 20-year follow-up ( n = 33), covering multiple domains. Psychiatric assessments occurred at eight time points. Cox proportional hazard models and linear mixed-effects models tested bidirectional associations between cognitive functioning and depression. Group-level cognitive change was tested using paired sample t -tests and Bayesian analyses, and individual-level change using reliable change indices (RCI’s). Results No cognitive domains significantly predicted time-to-depressive-relapse, the number of depressive episodes, or total time depressed over 20 years. Similarly, the number of episodes, total time depressed, and changes in depression severity did not significantly predict cognitive changes. At follow-up, we observed declines in speed of information processing ( p < .001, d = -0.73, RCI: 32.1% deteriorated) and speed of memory processing ( p = .015, d = -0.49, RCI: 39.3% deteriorated). Learning and memory improved ( p < .001, d = 1.19, RCI: 28.6% improved). Working memory and executive functioning remained stable. Findings were not explained by selective drop-out. Conclusions We found only minor long-term cognitive change, with no clear worsening or evidence of scarring and state effects. Cognitive functioning remained relatively stable, and we observed no link to depression trajectories over 20 years, providing a more optimistic outlook for depressed patients.